Analisis Perbandingan Metode Analytical Hierarchy Process ( Ahp) Dan Technique For Order Preference By Similarity To Ideal Solution (Topsis) Dalam Penentuan Penerima Bantuan Pkh - Amfotis, Maria Osti; Nababan, Darsono; Legu Rema, Yasinta Oktaviana; Ullu, Hevi Herlina (Jutis (Jurnal Teknik Informatika), 2023)
PKH is a program launched in 2007. The main aim of PKH is to work on the nature of human resources, especially in the fields of education and welfare for low-income families. . Distribution of PKH aid has also been distributed to North Central Timor Regency. Guarantees for social assistance recipients still use manual techniques which only carry out assessments without estimates so that aid is not distributed on track. Therefore, a system that facilitates the process for receiving PKH benefits is very important. Next, the researcher designed a system that supports making decisions using the Analytical Hierarchy Process (AHP) method and Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) with predetermined steps. These two approaches will be compared to determine the best method for PKH beneficiaries in the hope that this can help determine which beneficiary is more suitable and appropriate. This analysis was carried out by involving the degree of accuracy of each method in dealing with cases as a reference source. The similarity level effect of the AHP strategy is equivalent to TOPSIS so that both methodologies can be utilized in dealing with the problem of determining PKH recipients. Keywords: Analysis, PKH, AHP, TOPSIS, Website